The relevance of stornatal frequency, type and size in the delimitation of three complex species of Dioscoren L. (Dioscoreaceae) - Ugborogho, R.E.; Ng, N.Q.; Thottappilly, G.; Hahn, S.K. (1993)
The abaxial surfaces of the fresh leaves of 6 cultivars of Dioscorea alata L. (the water yam), 10 cultivars of D. cayenensis Lam. (the yellow yam) and 34 cultivars of D. rotundata Poir. (the white yam) were investigated for variations in the frequency, type and size of stomata. Eleven stomata types, namely anomocytic, anisocytic, contiguous, paracytic, staurocytic, dicytic, tricytic, tetracytic, pentacytic, hexacytic and septacytic were observed in both D. cayenensis and D. rotundata. Among these stomata types, the paracytic, dicytic and septacytic were not found in D. alata. On the whole, the sizes of stomata increased with increase in the number of epidermal cells surrounding the guard cells especially with reference to tricytic, tetracytic and pentacytic stomata. The mean stomatal frequency per microscopic field of 400 x in the three species were 177/mm2 in D. alata. 142/mm2 in D. cayenensis and 226/mm2 in D. rotundata while the overall means of stomatal length and breadth were 32.06 μm x 22.05 μm in D. alata and 34.50 μm x 23.42 μm in D. cayenensis and 34.07 μm x 22.76 μm in D. rotundata. On the basis of the mean stomatal lengths, D. alata was separated into two groups, D. cayennensis into three and D. rotundata into four. D. alata was separated from the other two species while D. cayennensis was recognized as a variable subspecies of D. rotundata.